Dietary format alters fecal bacterial populations in the domestic cat (Felis catus) - Bermingham EN; Young W; Kittelmann S; Kerr KR; Swanson KS; Roy NC; Thomas DG (John Wiley and Sons, 2013)
The effects of short-term (5-week) exposure to wet or dry diets on fecal bacterial populations in the cat were investigated. Sixteen mixed-sex, neutered, domestic short-haired cats (mean age = 6 years; mean bodyweight = 3.4 kg) were randomly allocated to wet or dry diets in a crossover design. Fecal bacterial DNA was isolated and bacterial 16S rRNA gene amplicons generated and analyzed by 454 Titanium pyrosequencing. Cats fed dry diets had higher abundances (P < 0.05) of Actinobacteria (16.5% vs. 0.1%) and lower abundances of Fusobacteria (0.3% vs. 23.1%) and Proteobacteria (0.4% vs. 1.1%) compared with cats fed the wet diet. Of the 46 genera identified, 30 were affected (P < 0.05) by diet, with higher abundances of Lactobacillus (31.8% vs. 0.1%), Megasphaera (23.0% vs. 0.0%), and Olsenella (16.4% vs. 0.0%), and lower abundances of Bacteroides (0.6% vs. 5.7%) and Blautia (0.3% vs. 2.3%) in cats fed the dry diet compared with cats fed the wet diet. These results demonstrate that short-term dietary exposure to diet leads to large shifts in fecal bacterial populations that have the potential to affect the ability of the cat to process macronutrients in the diet.
Keywords: Science & Technology; Life Sciences & Biomedicine; Microbiology; Feline; fecal bacterial community; high-throughput nucleotide sequencing; RIBOSOMAL-RNA SEQUENCES; MICROBIAL-POPULATIONS; GUT MICROBIOME; INTESTINAL MICROBIOTA; ADULT CATS; OBESITY; CONNECTION; DIVERSITY; CELLULOSE; TRACT; 0605 Microbiology